Maternal separation on the ethanol-preferring adult rat liver structure - Rosa-Toledo, Olegário [UNESP]; Almeida-Chuffa, Luiz G. [UNESP]; Martinez, Marcelo; Felipe-Pinheiro, Patricia F. [UNESP]; Padovani, Carlos R. [UNESP]; Martinez, Francisco E. [UNESP] (Elsevier, 2015)
Background and rationale for the study. We designed to test whether there is interaction of maternal separation (MS) on the ethanol-preferring rats liver structure. The UCh rat pups were separated daily from their mothers during the stress hyporesponsive period (SHRP), between four and 14 days-old, always at the same time for four hours in a cage containing eight subdivisions, one for each pup. Subsequently, rats that presented the highest (UChB) and the lowest (UChA) ethanol (EtOH) consumption were selected to the study. Both UChB and UChA rats received 10% (v/v) EtOH and distilled water ad libitum until the end of the experiment (120 days-old). The liver was collected to histological routine for morphometric and stereological analyses, and immunohistochemistry. There was an interaction of MS and EtOH on the liver: increased liver mass, peritubular vessels, stellate cell numbers, steatosis and cell death, decreased necrosis, sinusoidal capillary diameters and cell proliferation. While there was a decrease in FSH, testosterone and 5α-di-hidrotestosterone, and increasing corticosterone and cholesterol. There is interaction of MS and EtOH on the liver structure, dependent on the amount of EtOH intake. Furthermore, the interaction of stress and drugs can increase or decrease their effects on the liver or indirectly via hypothalamic-pituitary-adrenal (HPA) and hypothalamic-pituitary-gonadal (HPG) axes.